The secret language of dogs : unlocking the canine mind for a happier pet - Stilwell, Victoria (Ten Speed Press, an imprint of the Crown Publishing Group, 2016)
"Recent studies into the minds of canines show that they have a rich social intelligence and a physical and vocal language as complex and subtle as our own. In The Secret Language of Dogs, world-renowned trainer and star of Animal Planet's It's Me or the Dog Victoria Stilwell reveals how to both interpret and "speak" the hidden language of dogs. This book is your guide to understanding your pooch, communicating effectively, strengthening your bond, and helping dogs learn in the most effective way possible so they feel confident navigating the human world with success,"--Amazon.com.